Analisis Faktor -Faktor yang Mempengaruhi Pemahaman Pasien terhadap Informed Consent di Rumah Sakit - Dewangga Primananda Susanto; Bramantya Surya Pratama; Tuti Hariyanto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
The effect of patient safety in good hospitals are illustrated by a good informed consent process in accordance with applicable regulations. Not a few hospitals lost the process of good informed consent, so caught up in the legal process during the incident. This study aims to determine, analyze and examine the factors that affect the understanding of patient informed consent in RSU X. This research uses explorative research with descriptive approach. The respondents of this study were divided into two groups: in-patients and medical teams between nurses and doctors at Hospital X. This study found the root causes of informed consent in patient unresponsiveness after a questionnaire analysis and focus group discussion (FGD) at RSU X. The result is 1) There is no method / tool to facilitate health personnel in explaining, (2) No media from the hospital to facilitate, (3) No appointment of person in charge, (4) Awareness of informed consent does not exist, and (5) Lack of socialization of Standard Operational Procedure and no policies. The solution is the creation of a media to assist in improving the understanding of patient informed consent such as building model like photonovela.